Implementation of Trend Analysis to Fulfill Needs of Consumer Housing with Least Square Method - Anggara, Denny; Pratiwi, Dian; Rochman, Abdul (Penerbitan Universitas Trisakti, 2024)
In this era there are a lot of real estate that stands with attractive prices, facilities and home designs. Real Estate is a land and buildings on it and arranged in an orderly manner. With the rapid growth of society, it is very influential in buying ready-to-live houses that match the criteria and prices they want. However, many people have difficulty in finding a house ready to live in that fits the criteria and price range they want. Therefore, by making the Trend Analysis Application for Ready-to-occupy Houses, it can provide alternative choices to users according to the criteria that buyers want, such as having a garage, garden, building area, having how many floors and so on as well as the price they want. This application was developed using the Least Square Method Trend Analysis Method for datasets of ready-to-occupy houses collected from one housing estate agency. The steps carried out by the researchers started from collecting housing data, then the data was processed using the least square method with R- studio tools and then formulated into the PHP programming language to become a web program. After the web program was successfully built, researchers conducted a survey to determine the level of user satisfaction with the application, which was 77.8% of the 18 survey participants. Based on the presentation, it can be concluded that this research is feasible in providing home recommendations for customers.